A Multi-Year Study of GOES-13 Droplet Effective Radius Retrievals for Warm Clouds over South America and Southeast Pacific - Correia, Alexandre L.; Mendonça, Marina M. [UNESP]; Nobrega, Thiago F.; Pugliesi, Andre C.; Cecchini, Micael A. (MDPI, 2022)
Geostationary satellites can retrieve the cloud droplet effective radius (re ) but suffer biases from cloud inhomogeneities, internal retrieval nonlinearities, and 3-D scattering/shadowing from neighboring clouds, among others. A 1-D retrieval method was applied to Geostationary Operational Environmental Satellite 13 (GOES-13) imagery, over large areas in South America (5◦ N–30◦ S; 20◦–70◦ W), the Southeast Pacific (5◦ N–30◦ S; 70◦–120◦ W), and the Amazon (2◦ N–7◦ S; 54◦–73◦ W), for four months in each year from 2014–2017. Results were compared against in situ aircraft measurements and the Moderate Resolution Imaging Spectroradiometer cloud product for Terra and Aqua satellites. Monthly regression parameters approximately followed a seasonal pattern. With up to 108,009 of matchups, slope, intercept, and correlation for Terra (Aqua) ranged from about 0.71 to 1.17, −2.8 to 2.5 µm, and 0.61 to 0.91 (0.54 to 0.78, −1.5 to 1.8 µm, 0.63 to 0.89), respectively. We identified evidence for re overestimation (underestimation) correlated with shadowing (enhanced reflectance) in the forward (backscattering) hemisphere, and limitations to illumination and viewing configurations accessible by GOES-13, depending on the time of day and season. A proposition is hypothesized to ameliorate 3-D biases by studying relative illumination and cloud spatial inhomogeneity.
Keywords: Cloud effective radius; GOES; Microphysics; Remote sensing; Tropics